Age-Specific Acute Changes in Carotid–Femoral Pulse Wave Velocity With Head-up Tilt. (7th July 2020) - Pucci, Giacomo; Spronck, Bart; Avolio, Alberto P; Tap, Lisanne; Vaudo, Gaetano; Anastasio, Fabio; Van Den Meiracker, Anton; Mattace-Raso, Francesco
Abstract: BACKGROUND: Aortic stiffness as measured by carotid–femoral pulse wave velocity (cfPWV) is known to depend on blood pressure (BP), and this dependency may change with age. Therefore, the hydrostatic BP gradient resulting from a change in body posture may elicit a cfPWV change that is age-dependent. We aimed to analyze the relationship between BP gradient—induced by head-up body tilting—and related changes in cfPWV in individuals of varying age. METHODS: cfPWV and other hemodynamic parameters were measured in 30 healthy individuals at a head-up tilt of 0° (supine), 30°, and 60°. At each angle, the PWV gradient and resulting cfPWV were also estimated (predicted) by assuming a global nonlinear, exponential, pressure–diameter relationship characterized by a constant β 0, and taking into account that (diastolic) foot-to-foot cfPWV acutely depends on diastolic BP. RESULTS: cfPWV significantly increased upon body tilting (8.0 ± 2.0 m/s supine, 9.1 ± 2.6 m/s at 30°, 9.5 ± 3.2 m/s at 60°, P for trend <0.01); a positive trend was also observed for heart rate (HR; P < 0.01). When the observed, tilt-induced cfPWV change measured by applanation tonometry was compared with that predicted from the estimated BP hydrostatic gradient, the difference in observed-vs.-predicted PWV change increased nonlinearly as a function of age ( R 2 for quadratic trend = 0.38, P < 0.01, P vs. linear = 0.04). This result was unaffected by HR tilt-related variations ( R 2 for quadratic trend = 0.37, P < 0.01, P vs. linear = 0.04). CONCLUSIONS: Under a hydrostatic pressure gradient, the pulse wave traveling along the aorta undergoes an age-related, nonlinear PWV increase exceeding the increase predicted from BP dependency.